Evaluation of Environmental Worldview from the Perspectives of Undergraduate Students in N. Cyprus - Asilsoy, Buket; Laleci, Selin; Yıldırım, Sinem; Uzunoğlu, Kozan; Fuller, Özge Özden (European Journal of Sustainable Development, 2016)
In recent years, environmental issues have been under considerable debate within the scientific community. In this context, environmental worldview has become a significant area of focus. In the light of recent studies it is understood that there are disparate variables influencing environmental worldview. Additionally it has been suggested that environmental worldview is a variable influencing environmental behaviour itself. As it is a significant aspect among the younger generations to adopt an environmentally responsible lifestyle, this study aimed at understanding the impact of several demographic variables such as gender and nationality on environmental worldview. In this research, environmental behaviour is further examined within the university students in Nicosia. A total number of 111 undergraduate students were chosen for this research. In the first section, several subjects were asked about their environmental knowledge and awareness. In the second section, with the help of Dunlop and Van Liere’s New Environmental Paradigm (NEP) scale, environmental attitudes of participants were measured, in order to understand the level of their existing worldview. Keywords: Environmental Worldview, NEP Scale, Survey, Undergraduate Students, Nicosia, Cyprus